The lysosome-related characteristics affects the prognosis and tumor microenvironment of lung adenocarcinoma - Chang, Wuguang; Gao, Wuyou; Wu, Yawei; Luo, Bin; Zhong, Lekai; Zhong, Leqi; Lin, Wenqian; Wen, Zhesheng; Chen, Youfang (Frontiers in Medicine, 2025)
BackgroundThe lysosome plays a vitally crucial role in tumor development and is a major participant in the cell death process, involving aberrant functional and structural changes. However, there are few studies on lysosome-associated genes (LAGs) in lung adenocarcinoma (LUAD).MethodsBulk RNA-seq of LUAD was downloaded from The Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO). The lysosome risk signature was constructed after univariate and least absolute shrinkage and selection operator (Lasso) cox regression analysis of the TCGA training set, and its capability was validated by additional validation sets from GEO. Single cell sequencing (scRNA) was obtained from GEO to analyze the differences of lysosome risk signature at the single-cell level and the differences in the function and pathway. In vitro experiments have validated the function of CTSH in LUAD.ResultsThe risk signature contained seven key LAGs, and patients were categorized into high- and low-risk groups based on a specific calculation formula. The LAG risk signature, which accurately predicted the prognostic status of LUAD patients, was still regarded as an independent prognostic indicator in multifactorial cox regression analysis. Subsequently, the combination of the signature and key clinical information was used to construct a column-line diagram for clinical assessment, which had a high discriminatory power. Immune infiltration analysis from bulk RNA-seq and scRNA-seq indicated that the low-risk group was immune-activated and had a better benefit in the prediction of immunotherapy. Finally, we validated its role in inhibiting tumor proliferation and metastasis in LUAD cells by knockdown of CTSH.ConclusionWe defined a new biomarker that provided unique insights for individualized survival prediction and immunotherapy recommendations for LUAD patients.